1983
DOI: 10.1097/00004032-198301001-00046
|View full text |Cite
|
Sign up to set email alerts
|

Measured 234,238U and Fallout 239,240Pu in Human Bone Ash from Nepal and Australia

Abstract: Human bone samples from Nepal and Australia were analyzed for isotopic uranium and fallout plutonium. The Nepalese samples were obtained for a 3-yr period (197678) while the Australian samples are representative of a single year (1977). The surface air plutonium concentrations for the latitude bands of these countries were either measured and/or estimated from 1954 through 1978. With the plutonium air concentrations and age-dependent breathing rates as input data, the measured human bone results were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cesium-137 concentrations in Nepalese samples (93-417 Bq/kg) are comparable to those measured in Scandinavia (152-3466 Bq/kg), Italy (118-11,084 Bq/kg) and Antarctica (47-134 Bq/kg) (Triulzi et al, 1996). Other studies have also confirmed the contamination of the Himalayan region with cesium-137 (Balerna et al, 2003), as well as with strontium-90 and plutonium-239/240 (Fisenne et al, 1983). Human breast milk from Nepal has shown elevated levels of cesium-137 even 10 years after the Chernobyl accident (Lechner et al, 1997).…”
Section: Man-made (Fallout) Radionuclidesmentioning
confidence: 90%
See 2 more Smart Citations
“…Cesium-137 concentrations in Nepalese samples (93-417 Bq/kg) are comparable to those measured in Scandinavia (152-3466 Bq/kg), Italy (118-11,084 Bq/kg) and Antarctica (47-134 Bq/kg) (Triulzi et al, 1996). Other studies have also confirmed the contamination of the Himalayan region with cesium-137 (Balerna et al, 2003), as well as with strontium-90 and plutonium-239/240 (Fisenne et al, 1983). Human breast milk from Nepal has shown elevated levels of cesium-137 even 10 years after the Chernobyl accident (Lechner et al, 1997).…”
Section: Man-made (Fallout) Radionuclidesmentioning
confidence: 90%
“…As a result of global fallout, radioactive pollution is undoubtedly present in Nepal. Fisenne et al (1983) estimated cumulative plutonium doses received by bone cells among the dead human samples collected from Nepal and Australia, and the results indicate that there was higher plutonium fallout in Nepal than in Australia. The 1986 Chernobyl nuclear power plant accident in Ukraine further increased the environmental radioactivity into the global environment, with most of the fallout being noticed in Russia, Belarus, Ukraine, Scandinavia and other parts of Europe.…”
Section: Man-made (Fallout) Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation